Cultivation of Siberian Motherwort Plants (Leonurus sibiricus L.) in In Vitro Culture - Anna Figas; Magdalena Tomaszewska-Sowa; Zofia Gruszka (Agronomy)
In this study, an attempt was made to micropropagate the Siberian motherwort (Leonurus sibiricus L.) in in vitro cultures. The aim of this study was to compare methods of sterilization of seeds, which served as a source of initial explants to induce in vitro culture and to multiply shoots from explants isolated from them. The primary explants in the experiment were seeds. The seeds were placed on ½ MS medium without PGR and enriched with GA3 at a concentration of 1 mg∙dm−3. The addition of GA3 to the medium stimulated their germination. Sodium hypochlorite (NaClO) and 70% ethanol (C2H5OH) were used to sterilize the seeds. NaClO was used for proper sterilization in concentrations: 0.0% (1), 1.5% (2), 2% (3), and 2.5% (4) for 11 min. As secondary explants in the experiment, single-node fragments of sterile seedlings derived from sterile seeds were used, which were placed on MS medium, with the addition of plant growth regulators (PGR) from the group of auxins and cytokinins. The largest number of sterile and live Siberian motherwort seedlings was obtained in the variant in which 2.5% NaClO was used for proper sterilization of the seeds. To optimize the procedure of in vitro micropropagation, the axillary shoots of Leonurus sibiricus L. were transferred during the third passage onto nine different combinations of MS medium: PGR-free medium, with different concentrations of BAP (6-benzylaminopurine) (0.0, 2.0, 3.0, 4.0, 5.0 mg∙dm−3) and BAP (0.0, 2.0, 3.0, 4.0, 5.0 mg∙dm−3) with NAA (1-naphthaleneacetic acid) (1.0 mg∙dm−3). The largest number of shoots (9.62) forming was obtained on the medium supplemented with 4 mg∙dm−3 BAP and 1 mg∙dm−3 NAA, while the longest shoots were on the medium without PGR. Induction of rhizogenesis of Siberian motherwort plants in in vitro cultures was achieved on MS medium with the addition of 0.5 mg∙dm−3 IAA (indole-3-acetic acid). At the stage of adaptation to ex vitro conditions, high plant survival of 90% was achieved by using a solution with MS salts (25%) for irrigation.